Geochemical Peculiarities of Ores from the Largest Natalka Gold Deposit in Northeastern Russia - Volkov A.V.; Murashov K.Yu.; Sidorov A.A. (My University, 2016)
This study of the behavior of trace and rare earth elements in ores from the Natalka gold deposit allows us to draw several conclusions. It is suggested that ore formation is related to the regional metamorphism of the host terrigenous carbonaceous rocks, which could be the major source for trace and rare earth elements. Minor enrichment of the Natalka ores in W is evidence of the contribution of magmatic fluid, which could be superimposed on early quartz veins, in ore formation. Our results support the metamorphic–magmatic model of formation of economic gold–quartz deposits of the Yana–Kolyma Belt. The similarity of metasomatites of the Natalka deposit with disseminated gold–sulfide refractory ores from the Nezhdaninskoe and Bakyrchik deposits points to the possible presence of such ores in the Natalka deposit. Our data are important for forecasting regional metallogenic reconstructions, search, and evaluation of gold deposits.
Keywords: Natalka